MORMONISM AS MEME IN GOVERNMENT-SPONSORED INFORMATION OPERATIONS ON TWITTER - Greenhalgh, Spencer (TROPOS: COMUNICAÇÃO, SOCIEDADE E CULTURA (ISSN: 2358-212X), 2021)
A general suspicion of Mormonism in American politics and media dates back to the 19th century and continues today. Weber (2019) has described Mormonism as a "meme" that is malleable enough to symbolize different things for different audiences in different contexts. In this study, I examine the presence of "Mormonism as meme" in 511 posts composed by government-sponsored Twitter accounts as part of information operations before, during, and after the 2016 U.S. presidential election. I retrieved these posts from a dataset of government-sponsored tweets made available by Twitter and used a mix of computational and human methods to determine: 1) which countries used Mormonism as meme, 2) whether government-sponsored accounts originated or amplified these messages, 3) what identities government-sponsored accounts adopted, and 4) how government-sponsored accounts used Mormonism as a meme. This study's results indicate that six governments invoked Mormonism as part of their information operations during this time frame. Venezuela pursued a strategy that depended on using pro-Trump accounts to repeatedly share messages describing Mormons as communitarian and insular. Other countries (including Russia and Iran) pursued more subtle strategies, more often retweeting others' posts than writing their own. However, they still invoked aspects of Mormonism that called into question its compatibility with liberal, conservative, or broadly American values. As a whole, these posts correspond with both Weber's (2019) description of Mormonism as malleable meme and information operations' twin purposes of influencing the 2016 election and dividing Americans.